Techno-economic analysis of the integrated DME production process: Effects of different separation trains and recycling strategies - Park, Hyeon; Bae, Jong Wook; Kim, Gookhee; Park, Myung June (Korean Journal of Chemical Engineering, 2022)
Integrated process models were developed to produce dimethyl ether (DME) from the byproduct gas of the steelmaking process. Two different separation trains (the use of flash drums to separate light gases followed by two columns to separate CO2 and DME vs. the application of an absorber to separate light gas and CO2 under mild temperatures), and two different recycling strategies (recycling with and without further separation of hydrogen by a membrane) were considered. Detailed kinetic reactions for methanol (MeOH) synthesis from syngas and the dehydration of MeOH to DME were used in the reactor model, which helped predict the compositions of the reactor effluent under various conditions and determine the operating conditions of the separation trains. Both separation trains with recycled stream increased the DME production rate and overall CO2 conversion, while the sizes of the reactor and separators, and the utility costs of refrigeration, absorbent recovery, recycled stream compression, etc. were significantly increased. The tradeoffs between different cases were quantitatively analyzed by techno-economic and sensitivity analyses. The results showed that the use of the absorber with the recycling of hydrogen is the most feasible process for the economic production of DME with high CO2 reduction.
Keywords: CO2 Reduction; Detailed Kinetic Rates; Dimethyl Ether; Recycling; Separation Trains; Techno-economic Analysis